2022
DOI: 10.3390/ani13010025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Nutritional Value and Degradation Characteristics of Amaranth Hay in the Rumen of Goats at Different Growth Stages

Abstract: The objective of this study was to investigate the rumen degradation characteristics of grain amaranth hay (Amaranthus hypochondriacus) at four different growth stages. The aim of this study was to evaluate the nutritional value of grain amaranth hay at different growth stages by chemical composition, in vivo digestibility, and in situ degradability. Three Boer goats with permanent ruminal fistulas were selected in this study. Amaranthus hay at four different growth stages (squaring stage (SS), initial bloom s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Likewise, the CP degradation rate in the rumen of the LBC group displayed the maximum value. Previously, a study found that higher CP content in roughage was beneficial for improving ruminal CP degradation [44], which is in line with our findings. The ruminal CP degradability is related to the true protein content of the roughage, and the amino acid composition of CP in roughage can also influence the ruminal CP degradation rate [45].…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, the CP degradation rate in the rumen of the LBC group displayed the maximum value. Previously, a study found that higher CP content in roughage was beneficial for improving ruminal CP degradation [44], which is in line with our findings. The ruminal CP degradability is related to the true protein content of the roughage, and the amino acid composition of CP in roughage can also influence the ruminal CP degradation rate [45].…”
Section: Discussionsupporting
confidence: 93%
“…The degradation of CP in the rumen is influenced by various factors, including the structural composition of fiber and protein in roughage [29], as well as the capacity of the host's rumen microbiota to utilize roughage [30]. Research has shown that feeds with high CP content usually led to higher rumen degradability [31]. However, in this study, we…”
Section: Discussionmentioning
confidence: 79%
“…The degradation of CP in the rumen is influenced by various factors, including the structural composition of fiber and protein in roughage [ 29 ], as well as the capacity of the host’s rumen microbiota to utilize roughage [ 30 ]. Research has shown that feeds with high CP content usually led to higher rumen degradability [ 31 ]. However, in this study, we found that CP content of GS was significantly higher than that of AS, but the ED of CP and the degradation rate of 36 to 72 h in AS were significantly higher than those in GS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is urgent to develop roughage resources which can replace alfalfa in the ration of dairy cows under modern large-scale intensive dairy farming. A previous study used Boer goats with permanent ruminal fistulas as experimental animals and found that the ruminal effective degradability of dry matter (DM) and CP were approximately 67% and 75%, respectively [ 9 ]. However, the information of amaranth hay replacing alfalfa hay in the diet of dairy cows remains scarce.…”
Section: Introductionmentioning
confidence: 99%